Identifying Recruitment Sources Across Trophic Levels in a Large River Food Web - Shaley A. Valentine; Kristen L. Bouska; Gregory W. Whitledge (Ecology and Evolution)
ABSTRACT Assemblages are connected through the movement of physical and biological resources including recruits. Identifying recruitment sources for predators and their prey could help us understand how assemblages use connectivity across multiple trophic levels and whether predator and prey recruitment is coupled. Recruitment sources of organisms across multiple trophic levels can be quantified by trace element analysis of stomach contents. We used trace element analysis of otoliths to determine recruitment contributions from tributaries of predatory largemouth bass (Micropterus salmoides) and bowfin (Amia calva) and their consumed prey collected from Pools 4, 8, and 13 of the Upper Mississippi River. We used laser ablation inductively coupled mass spectrometry to quantify strontium:calcium of the core of each otolith and classified each fish to a natal origin (i.e., tributary or potential resident). We compared patterns of natal origin across study reaches, collection years, and species and with previously published origins of independently sampled prey fish. Predator and prey assemblages across all study reaches recruited from tributaries. More prey (44%) than predators (17%) recruited from tributaries. Of fishes originating from tributaries, individuals recruited from various rivers including the large Minnesota and Wisconsin Rivers and several small tributaries. Patterns in natal origin were similar among predators and prey families and among reaches, across sampling years, and between consumed prey and independently sampled prey. Tributaries consistently contributed recruits to both prey and predator fishes, leading to a coupling of predator and prey recruitment sources across space and time. Predators directly and indirectly used tributaries for recruitment and persistence through their own and their prey's recruitment. We further highlighted the utility of using consumed prey to simultaneously study the ecology of prey and predator assemblages, thereby reducing research sampling needs.